On the denial of recognition in spain of a protective measure contained in an arbitral award in bankruptcy issued in the Russian Federation - Iriarte Ángel, José Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This article addresses the problem of the recognition and execution in Spain of a protective measure issued in Russia in an arbitration procedure of a bankruptcy nature. The Spanish Court applies the New York Convention of June 10, 1958 to the case without any specific justification as if it were assumed that the exequatur of an arbitration protective measure is governed by it. It rejects the plaintiff’s claim for two reasons, failure to submit the arbitration agreement and that the decision falls on a matter that under our legal system can not be submitted to arbitration.